2020
DOI: 10.1111/dth.13467
|View full text |Cite
|
Sign up to set email alerts
|

Biologics for psoriasis in COVID ‐19 era: What do we know?

Abstract: We have read with great interest the article by Conforti et al who stressed the importance of a therapeutic reassessment of all psoriatic patients, chronically treated with immunosuppressive drugs in the pandemic coronavirus disease (COVID)-19 era. 1 In the context of dermatology, psoriasis patients represent an important subset since their prevalence (125 million worldwide). The literature, mass media, and information campaigns are daily focusing on preventive measures, risk factors, and class of subjects whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 7 publications
3
24
0
Order By: Relevance
“…Prior studies have not shown worsen COVID-19 outcomes among psoriasis patients on biologics. [5][6][7] A large Italian study did not detect ICU admissions or deaths suspected for COVID-19. 8 Few studies evaluated conventional systemic therapies.…”
mentioning
confidence: 99%
“…Prior studies have not shown worsen COVID-19 outcomes among psoriasis patients on biologics. [5][6][7] A large Italian study did not detect ICU admissions or deaths suspected for COVID-19. 8 Few studies evaluated conventional systemic therapies.…”
mentioning
confidence: 99%
“…In such a context, dupilumab will prove to be effective. Also, it needs to be borne in mind that anti-drug antibodies or neutralizing antibodies could be generated during the period of discontinuation that could eventually render the treatment useless at a later stage [12]. Knowledge of immunological pathways also has shown that the pathways of IL-4 and IL-13, which are Th2 cytokines, have not been implicated in host defense mechanisms against viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to stop or modify the drug regimen could be guided by the disease severity, presence of psoriatic arthritis, comorbid conditions conferring higher risk for COVID-19, and the risk of exposure to COVID-19 based on community prevalence. [ 29 ] Therefore, patients with erythrodermic, pustular, extensive psoriasis, or psoriatic arthritis with no risk factors for COVID-19 may be initiated on immunosuppressive therapy after informed consent and counseling for necessary precautions.…”
Section: Psoriasismentioning
confidence: 99%
“…In case of extensive, severe, or unresponsive disease, drugs with known efficacy in psoriasis like acitretin or small molecules like apremilast that have a shorter half-life as compared to most biologics may be preferred. [ 8 29 ] Hydroxychloroquine sulphate used for prophylaxis and treatment of COVID-19 may potentially cause disease exacerbation in patients with psoriasis. The exact risk of psoriasis induction or exacerbation with antimalarials is unkown.…”
Section: Psoriasismentioning
confidence: 99%
See 1 more Smart Citation